CLEISTANTHIN B SHOWS A POTENT CYTOTOXIC ACTIVITY AGAINST COLORECTAL CANCER CELLS - SAGAR, PULI; RAVEENDRAN, RAMASAMY (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The aim was to find out the cleistanthin B sensitive cancer cell type among a panel of cancer cell lines. Methods: The 50% inhibitory concentrations (IC50) of cleistanthin B against different cancer cells were determined by 3-(4,5-dimethylthiazol-2-yl)- 2,5-diphenyltetrazolium bromide assay. The cell death caused by cleistanthin B in colorectal cancer (CRC) cells was evaluated by acridine orange and ethidium bromide (AO-EB) dual staining. Using short exposure, we generated the 5-fluorouracil</AQ1> and oxaliplatin (5-FU+Ox) surviving cells from the parental HT-29 CRC cell lines. These surviving CRC cells were further treated with cleistanthin B either alone or combined with 5-FU. Annexin V apoptosis assay was used to determine the combined effect of cleistanthin B with 5-FU against HT-29 cells. Results: The IC50 values of cleistanthin B were found to be 3.6±0.55, 5.2±0.51, 8.6±1.02, 10.5±1.50, 18.3±3.71, 25.8±5.50, and 26.7±5.90 μg/mL against HT-29, SW-480, HCT-15, HELA, MDA-MB-231, A549, and DU145, respectively. The IC50 value of cleistanthin B against L132 cells was >100 μg/mL. The cleistanthin B treated HT-29, SW-480, and HCT-15 CRC cells showed apoptotic changes such as chromatin condensation, nuclear fragmentation, and formation of apoptotic bodies in the AO-EB dual staining method. Flow cytometry analysis revealed that cleistanthin B enhances the 5-FU induced apoptosis against 5-FU+Ox surviving HT-29 CRC cells. Conclusion: Cleistanthin B is relatively more potent against CRC cells than other cancer cells, and it induces apoptosis mediated cell death in CRC cells. Cleistanthin B enhances the anticancer activity of 5-FU against HT-29 CRC cells.